The Aedes aegypti mosquito evolves two types of prophenoloxidases with diversified functions - Xiaojing Zhu; Lei Zhang; Linlong Jiang; Huaqing Chen; Yu Tang; Xiaoyun Yang; Pengkun Bao; Chenghong Liao; Jianyong Li; Christopher J. Vavricka; Delin Ren; Zhaohui Chen; et al. (Proceedings of the National Academy of Sciences, 2025)
Insect phenoloxidase, presented as an inactive precursor prophenoloxidase (PPO) in hemolymph, catalyzes melanin formation, which is involved in wound healing, pathogen killing, reversible oxygen collection during insect respiration, and cuticle and eggshell formation. Mosquitoes possess 9 to 16 PPO members across different genera, a number that is more than that found in other dipteran insects. However, the reasons for the redundancy of these PPOs and whether they have distinct biochemical properties and physiological functions remain unclear. Phylogenetic analysis confirmed that Aedes aegypti PPO6 (Aea-PPO6) is an ortholog to PPOs in other insect species, classified as the classical insect type, while other Aea-PPOs are unique to Diptera, herein referred to as the dipteran type here. We characterized two Aea-PPO members, Aea-PPO6, the classical insect type, and Aea-PPO10, a dipteran type, which exhibit distinct substrate specificities. By resolving Aea-PPO6’s crystal structure and creating a chimera protein (Aea-PPO6-cm) with Motif 1 ( 217 GDGPDSVVR 225 ) from Aea-PPO10, we identified the motif that determines PPO substrate specificity. In vivo, loss of Aea-PPO6 led to larval lethality, while Aea-PPO10 was involved in development, pigmentation, and immunity. Our results enhance the understanding of the functional diversification of mosquito PPOs.